Сlassification methodology e-mails using neural networks - Терейковський, Ігор Анатолійович (Ukrainian Information Security Research Journal, 2013)
The effectiveness of email security is largely dependent on the accuracy of spam detection in leaves and roots. Existing recognition methods based on statistical analysis of text information, which significantly limits their ability to detect new types of spam and leaks. To overcome this shortcoming proposed classification methodology sheets based on semantic analysis using an electronic neural networks. A used as input parameters of the neural network in the frequency of meeting the letter of informative words in canonical form. It is shown that the best type of neural network model is Kohonen map, the main advantage of which is a high-speed training and the possibility of easy visualization of classification. This allows you to quickly react to new spam and howl leaks and conduct a final classification of letters by the user. The experiments confirmed the possibility of increasing the reliability of detection of 20-30%